A Review of Analytical Platforms for Accurate Bile Acid Measurement - Dutta, Mainak (Anal Bioanal Chem, 2019)
Bile acids are acidic steroids which help in lipid absorption, act as signaling molecules, and are key intermediate molecules between host and gut microbial metabolism. Perturbations in the circulating bile acid pool can lead to dysregulated metabolic and immunological function which often cause liver and intestinal diseases. Bile acids have chemically diverse structures and are present in broad range of biological concentrations in a wide variety of samples with complex biological matrices. Advanced analytical methods are therefore required to identify and accurately quantify individual bile acids. Though enzymatic determination of total bile acid is most popular in clinical laboratories, these methods provide limited information about individual bile acids. Advanced analytical methods such as gas chromatography- and liquid chromatography-mass spectrometry and nuclear magnetic resonance spectroscopy have now emerged as highly informative techniques which help in identification and quantification of individual bile acids in complex biological matrices. Here, we review the detection technologies currently used for bile acid identification and quantification. We further discuss the advantages and disadvantages of these analytical techniques with respect to sensitivity, specificity, robustness, and ease of use.